Aluminum-containing insulation-coated soft magnetic composite material and method for manufacturing the same

CN122950295APending Publication Date: 2026-10-20NORTHEASTERN UNIV CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611434094.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

针对软磁复合材料中软磁粉末颗粒间绝缘性不足,以及含铝无机绝缘包覆过程中铝源水解速度较快、易形成游离沉淀和磁粉表面沉积不均匀等问题,本发明提供一种含铝绝缘层包覆的软磁复合材料及其制备方法

Benefits of technology

1.本发明选择冰乙酸作为异丙醇铝的络合调控剂。冰乙酸含水量较低,能够避免在络合调控阶段提前引入大量未经计量的水;冰乙酸中的乙酸根能够与异丙醇铝的铝中心发生配位,形成水解活性相对较低的含乙酸根改性铝醇盐物种,从而减缓异丙醇铝与水接触后的水解速率,减少含铝物种在溶液中快速均相成核并形成游离沉淀的倾向。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention belongs to the field of soft magnetic composite material preparation technology, and discloses a soft magnetic composite material coated with an aluminum insulating layer and its preparation method. Pre-dried soft magnetic powder is dispersed in anhydrous ethanol and subjected to ultrasonic treatment; aluminum isopropoxide is dissolved in isopropanol, hydrolysis is controlled by adding glacial acetic acid, and then deionized water diluted with isopropanol is added to obtain an aluminum-containing precursor solution; the aluminum-containing precursor solution is added to a magnetic powder suspension, causing the aluminum-containing hydrolysis products to deposit on the surface of the magnetic powder. After the reaction, no solid-liquid separation or washing is performed; the solvent is directly evaporated, and after drying, grinding, and sieving, annealing is carried out under nitrogen protection to nanocrystallize the soft magnetic powder and form an aluminum-containing insulating layer. The theoretical Al2O3 content is 0.2%~1.2% of the magnetic powder mass. After resin coating, granulation, pressing, and low-temperature heat treatment, the obtained powder can effectively reduce the high-frequency power loss of the soft magnetic composite material, and the process is simple and suitable for large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of soft magnetic composite material preparation technology, specifically to a soft magnetic composite material coated with an aluminum insulating layer and its preparation method. Background Technology

[0002] As power electronic devices evolve towards higher frequencies, smaller sizes, and higher power densities, higher demands are placed on the high-frequency magnetic properties, power losses, and DC bias performance of soft magnetic materials. Soft magnetic composite materials are typically produced by bonding, granulating, and pressing soft magnetic powders with insulating properties. They possess advantages such as isotropy, ease of molding, and suitability for complex magnetic circuit structures, and are widely used in electronic devices such as power inductors, filters, and transformers. However, due to the direct contact between magnetic powder particles, interparticle eddy currents are easily formed under high-frequency alternating magnetic fields, leading to increased power losses in the magnetic powder core. Therefore, it is usually necessary to form an insulating layer on the surface of the soft magnetic powder to increase interparticle resistance and suppress eddy current losses.

[0003] Existing insulation treatments for soft magnetic powders mainly include phosphate coating, organic resin coating, inorganic oxide coating, and organic-inorganic composite coating. For example, Chinese invention patent application CN108242311A discloses a method for preparing a coated soft magnetic powder core, which first uses a phosphoric acid ethanol solution to phosphate the metal soft magnetic powder, then forms a manganese-zinc ferrite coating layer on the surface of the phosphated magnetic powder, and adds silicone resin before pressing and annealing; Chinese invention patent application CN111354528A discloses a phosphate-silane co-coated metal soft magnetic composite material and its preparation method, which forms an inorganic-organic composite insulating coating layer on the surface of the metal soft magnetic powder through phosphoric acid and silane; Chinese invention patent application CN110434326A discloses a method for in-situ coating a lithium aluminum oxide insulating layer on the surface of metal soft magnetic powder, which forms a lithium aluminum hydroxide precursor on the surface of the metal soft magnetic powder through a hydrothermal reaction, and then forms a lithium aluminum oxide insulating layer through high-temperature calcination.

[0004] The aforementioned existing technologies can improve the resistance between soft magnetic powder particles and reduce interparticle eddy current losses to a certain extent, but there is still room for further improvement. Phosphating and some organic-inorganic composite coating processes typically involve multiple steps such as coating solution preparation, reaction, drying, and subsequent resin treatment; the heat resistance of the organic components is relatively limited, which may restrict the temperature that can be used for subsequent stress-relief annealing or crystallization annealing of soft magnetic powder. Hydrothermal inorganic coating processes require hydrothermal reaction equipment and usually need to be combined with subsequent calcination treatment, making the process conditions and preparation flow relatively complex.

[0005] In the process of forming an inorganic insulating layer using metal alkoxide precursors, the reaction state of the precursor is easily affected by factors such as the amount of water added, reaction temperature, feeding rate, and system composition. When the reaction rate is too fast, the salt-containing hydrolysis products tend to condense and form free particles or agglomerates in the liquid phase, reducing the amount of salt-containing substances that can participate in the surface coating of soft magnetic powder. Insufficient reaction degree, on the other hand, is not conducive to the formation of an effective precursor coating structure on the surface of soft magnetic powder. Therefore, it is necessary to control the reaction process and addition method of the salt-containing precursor so that the salt-containing hydrolysis products can participate in surface coating under conditions of sufficient contact with the soft magnetic powder.

[0006] Furthermore, some inorganic insulating coating methods also include solid-liquid separation, washing, drying, and separate high-temperature conversion processes. For soft magnetic powders requiring stress-relief annealing or crystallization annealing, if the inorganic treatment of the precursor coating layer and the heat treatment required by the soft magnetic powder itself are performed separately, the number of heat treatments and the process flow will increase. Therefore, it is necessary to provide a method for preparing soft magnetic composite materials with a controllable coating process, suitable for soft magnetic powders, and capable of reducing solid-liquid separation, washing, and repeated heat treatment steps, thereby simplifying the preparation process and reducing the high-frequency power loss of the resulting soft magnetic material. Summary of the Invention

[0007] (I) The technical problems to be solved; To address the issues of insufficient insulation between soft magnetic powder particles in soft magnetic composite materials, as well as the rapid hydrolysis of aluminum source, easy formation of free precipitates, and uneven deposition on the magnetic powder surface during the aluminum-containing inorganic insulation coating process, this invention provides a soft magnetic composite material coated with an aluminum-containing insulating layer and its preparation method.

[0008] This invention regulates the hydrolysis reaction of aluminum source by using a complexing agent, and slowly adds deionized water diluted with an alcohol solvent to the aluminum source solution to induce controlled pre-hydrolysis of the aluminum source; then, aluminum-containing hydrolysis products are deposited on the surface of soft magnetic powder, and the aluminum-containing precursor coating layer undergoes an inorganic transformation through heat treatment; the resulting coated powder is then subjected to bonding, granulation, pressing and curing treatments to obtain a soft magnetic composite material coated with an aluminum insulating layer.

[0009] (II) Technical Solution; To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing a soft magnetic composite material coated with an aluminum insulating layer, comprising the following steps: Step S1: Pre-dry the soft magnetic powder and add anhydrous ethanol and stir to obtain a soft magnetic powder suspension; add aluminum isopropoxide to isopropanol, then add glacial acetic acid and stir to obtain an aluminum source solution; dilute deionized water with isopropanol and add it to the aluminum source solution and stir to obtain an aluminum-containing precursor solution. Step S2: Add the aluminum-containing precursor liquid to the soft magnetic powder suspension, and age it after stirring under heating conditions; After aging, the reaction system is not subjected to solid-liquid separation and washing. Instead, the solvent in the reaction system is directly evaporated by heating and stirring of the suspension. After drying, soft magnetic powder with an aluminum-containing precursor coating structure is obtained. Step S3: Under a protective atmosphere, the soft magnetic powder with an aluminum-containing precursor coating structure is heat-treated to obtain a soft magnetic powder with an aluminum insulating layer coating. Step S4: Mix the soft magnetic powder with aluminum insulating layer and binder in an organic solvent, so that the binder is distributed on the surface of the soft magnetic powder with aluminum insulating layer. Remove the organic solvent and dry it to obtain a soft magnetic powder with a multi-layer coating structure. Step S5: Press the soft magnetic powder with a multi-layer coating structure on the surface into shape, and anneal it in a protective gas atmosphere to obtain a soft magnetic composite material with an aluminum insulating layer.

[0010] The soft magnetic powder is selected from iron-based soft magnetic powder.

[0011] The iron-based soft magnetic powder is selected from one or more of the following: Fe-Si soft magnetic powder, Fe-Si-Al soft magnetic powder, Fe-Si-Cr soft magnetic powder, Fe-Ni soft magnetic powder, and Fe-Co soft magnetic powder.

[0012] In step S1, the mass ratio of the soft magnetic powder to the volume of anhydrous ethanol is 1g:3mL to 6mL.

[0013] The amount of aluminum isopropoxide added is determined according to the theoretical mass of Al2O3 obtained from its complete conversion, and the theoretical mass of Al2O3 is 0.2% to 1.2% of the mass of the soft magnetic powder; the molar ratio of aluminum isopropoxide, glacial acetic acid and deionized water is 1:0.8 to 1.2:2.5 to 3.5; the mass ratio of the soft magnetic powder to the volume of isopropanol used to disperse or dissolve aluminum isopropoxide is 1g:1mL to 3mL, and the mixture is stirred at 20℃ to 30℃ for 20min to 40min; then glacial acetic acid is added and stirring is continued for 20min to 40min to obtain the aluminum source solution; the mass ratio of the soft magnetic powder to the volume of isopropanol used to dilute the deionized water is 1g:0.5mL.

[0014] The aluminum-containing precursor solution is added to the soft magnetic powder suspension for 10 to 15 minutes; after addition, the mixture is reacted at 40 to 50 degrees Celsius with continuous stirring for 1 to 2 hours, followed by static aging for 20 to 30 minutes.

[0015] When the soft magnetic powder is FeSiBCuNb amorphous soft magnetic powder, the heat treatment is carried out under a nitrogen protective atmosphere, with the temperature increased to 580℃~620℃ at a heating rate of 2℃ / min~6℃ / min, held for 2h~4h, and then cooled in the furnace.

[0016] A soft magnetic composite material coated with an aluminum insulating layer is prepared by a specific method. The soft magnetic composite material covered by the aluminum-containing insulating layer includes soft magnetic powder particles, an aluminum-containing inorganic insulating layer disposed on the surface of the soft magnetic powder particles, and a binder distributed on the surface of the soft magnetic powder particles and between adjacent soft magnetic powder particles.

[0017] The soft magnetic powder particles are FeSiBCuNb nanocrystalline soft magnetic powder particles, the aluminum-containing inorganic insulating layer is an aluminum oxide-containing inorganic insulating layer, and the binder is a modified organosilicon resin.

[0018] (III) Beneficial Effects; Compared with the prior art, the present invention has the following beneficial effects: 1. This invention selects glacial acetic acid as a complexation regulator for aluminum isopropoxide. Glacial acetic acid has a low water content, which avoids the premature introduction of a large amount of unmeasured water during the complexation regulation stage; the acetate ions in glacial acetic acid can coordinate with the aluminum centers of aluminum isopropoxide to form acetate-modified aluminum alkoxide species with relatively low hydrolytic activity, thereby slowing down the hydrolysis rate of aluminum isopropoxide after contact with water and reducing the tendency of aluminum-containing species to rapidly and homogeneously nucleate and form free precipitates in solution.

[0019] 2. In this invention, deionized water is diluted with isopropanol and then slowly added to the aluminum source solution. The molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water is controlled within a suitable range. This reduces the local water concentration in the reaction system during water addition, thus coordinating the degree of complexation modification, hydrolysis degree, and hydrolysis rate of aluminum isopropoxide. This helps maintain aluminum-containing species in a suitable reaction state for surface deposition, promotes the deposition of aluminum-containing hydrolysis products on the surface of soft magnetic powder, and improves the uniformity and integrity of the aluminum-containing precursor coating layer.

[0020] 3. In this invention, an aluminum-containing precursor solution is slowly added to a soft magnetic powder suspension, and the reaction is carried out at 40°C–50°C with continuous stirring. Appropriate heating promotes the hydrolysis, condensation, and surface deposition of aluminum-containing species, while continuous stirring keeps the soft magnetic powder in suspension and dispersion, reducing local concentration differences in the reaction system. This reduces the tendency for soft magnetic powder to settle, accumulate local coatings, and aggregate between particles. Preferably, the reaction is carried out with continuous stirring at 45°C to coordinate the reaction rate, solution stability, and the soft magnetic powder surface deposition process.

[0021] 4. This invention eliminates solid-liquid separation and washing after the coating reaction. Instead, it directly evaporates the solvent in the reaction system through heating and stirring. This reduces the loss of deposited or still dispersed aluminum-containing precursors during filtration, centrifugation, and washing, improving the effective utilization rate of the aluminum source and maintaining the correlation between the amount of aluminum isopropoxide added and the amount of aluminum-containing material ultimately retained in the soft magnetic powder system. Furthermore, this treatment method reduces the need for solid-liquid separation and washing steps.

[0022] 5. This invention utilizes heat treatment under a protective atmosphere to dehydrate, decompose, and inorganically transform the aluminum-containing precursor coating layer on the surface of soft magnetic powder, forming an aluminum-containing inorganic insulating layer with good heat resistance and electrical insulation. This aluminum-containing inorganic insulating layer can create an electrical insulating barrier between adjacent soft magnetic powder particles, reducing direct conductive contact between particles and thus helping to suppress interparticle eddy current losses generated in the soft magnetic composite material under alternating magnetic field conditions.

[0023] 6. In this invention, a binder is further added to the surface of soft magnetic powder coated with an aluminum-containing inorganic insulating layer, and then granulated, pressed, and cured to form a soft magnetic composite material. The aluminum-containing inorganic insulating layer and the binder together constitute an inorganic-organic composite insulation system. The aluminum-containing inorganic insulating layer is used to improve interparticle insulation and heat resistance stability, while the binder is used to further isolate adjacent soft magnetic powder particles and improve the structural stability of the soft magnetic composite material after pressing, thereby taking into account both interparticle insulation performance and molding performance.

[0024] 7. When the soft magnetic powder is an iron-based amorphous soft magnetic powder, the present invention can simultaneously complete the nanocrystallization of the iron-based amorphous soft magnetic powder and the inorganic transformation of the aluminum-containing precursor coating layer through a single heat treatment, eliminating the need for a separate high-temperature conversion step for the aluminum-containing insulating layer in addition to crystallization annealing. This allows for the formation of an aluminum-containing inorganic insulating layer on the surface of the soft magnetic powder particles while simultaneously forming a nanocrystalline structure, combining the soft magnetic powder structure control process with the inorganic insulating layer formation process.

[0025] 8. Experimental results show that, when using FeSiBCuNb amorphous soft magnetic powder, and when the theoretical Al2O3 content is 0.2% to 1.2% of the mass of the soft magnetic powder, the power loss of the obtained soft magnetic composite material under the conditions of 20mT, 1MHz and 50mT, 500kHz is lower than that of the comparative example without aluminum insulation coating, and the permeability is still at a level similar to that of the comparative example. This indicates that the present invention can reduce high-frequency power loss while maintaining the basic stability of the permeability of the soft magnetic composite material.

[0026] 9. Within the tested theoretical Al2O3 content range, the power loss of the soft magnetic composite material generally showed a trend of first decreasing and then increasing. When the theoretical Al2O3 content was 0.8%, the power loss of the obtained soft magnetic composite material under 20mT and 1MHz conditions was reduced by approximately 39.66% compared to the control without aluminum insulation coating. This indicates that controlling the aluminum insulation layer content within a suitable range is beneficial for maintaining the overall magnetic properties of the soft magnetic composite material while improving interparticle insulation performance. Attached Figure Description

[0027] Figure 1 This is a process flow diagram of the preparation method of a soft magnetic composite material with an aluminum insulating layer according to the present invention. Detailed Implementation

[0028] To make the technical solution, objective, and beneficial effects of this invention clearer, the invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of this invention.

[0029] Unless otherwise stated, all percentage contents mentioned in this invention are mass percentage contents; the amount of raw materials used in this invention can be scaled up or down by the same proportion.

[0030] In a first aspect, the present invention provides a method for preparing a soft magnetic composite material coated with an aluminum insulating layer, comprising the following steps: Step S1: Pre-dry the soft magnetic powder, then add anhydrous ethanol for stirring and ultrasonic dispersion to obtain a soft magnetic powder suspension; Aluminum isopropoxide was added to isopropanol, and glacial acetic acid was added and stirred to control the complexation, thus obtaining an aluminum source solution. Deionized water was diluted with isopropanol and then added to the aluminum source solution and stirred to allow aluminum isopropoxide to undergo controlled pre-hydrolysis, thus obtaining an aluminum-containing precursor solution. Step S2: Add the aluminum-containing precursor liquid to the soft magnetic powder suspension and react under stirring and heating conditions to deposit the aluminum-containing hydrolysis products on the surface of the soft magnetic powder to form an aluminum-containing precursor coating layer. Then, age the powder. After aging, do not perform solid-liquid separation and washing on the reaction system. Instead, directly evaporate the solvent in the reaction system by heating and stirring. Then, dry, grind and sieve the powder to obtain soft magnetic powder with an aluminum-containing precursor coating structure on the surface. Step S3: Under a protective atmosphere, the soft magnetic powder with an aluminum-containing precursor coating structure is heat-treated to cause the aluminum-containing precursor coating structure to undergo dehydration, decomposition and inorganic transformation, forming an aluminum-containing inorganic insulating layer, and obtaining soft magnetic powder coated with an aluminum-containing insulating layer. Step S4: Mix the soft magnetic powder coated with the aluminum insulating layer and the binder in an organic solvent, so that the binder is distributed on the surface of the soft magnetic powder coated with the aluminum insulating layer, and then remove the organic solvent and dry it. The dried soft magnetic powder is granulated to obtain a soft magnetic powder with a multi-layered surface coating structure. Step S5: Press the soft magnetic powder with a multi-layer coating structure to obtain a soft magnetic composite material blank; under a protective atmosphere, cure and anneal the soft magnetic composite material blank, and then cool it to obtain a soft magnetic composite material with an aluminum insulating layer.

[0031] Furthermore, the soft magnetic powder is selected from iron-based soft magnetic powder.

[0032] Furthermore, the iron-based soft magnetic powder is selected from one or more of Fe-Si soft magnetic powder, Fe-Si-Al soft magnetic powder, Fe-Si-Cr soft magnetic powder, Fe-Ni soft magnetic powder, and Fe-Co soft magnetic powder.

[0033] Preferably, the soft magnetic powder is FeSiBCuNb amorphous soft magnetic powder.

[0034] Furthermore, the soft magnetic powder is pre-dried in air at 60°C–70°C for 1–3 hours. This pre-drying is used to reduce the impact of adsorbed water on the surface of the soft magnetic powder on the subsequent controlled hydrolysis process of aluminum isopropoxide.

[0035] Preferably, the soft magnetic powder is pre-dried at 65°C for 2 hours.

[0036] Furthermore, the mass ratio of the soft magnetic powder to the volume of anhydrous ethanol is 1g:3mL to 6mL; the total ultrasonic dispersion time is 5min to 10min.

[0037] Preferably, the mass ratio of the soft magnetic powder to the volume of anhydrous ethanol is 1 g: 4.5 mL. The soft magnetic powder is first thoroughly wetted by mechanical stirring, then ultrasonically dispersed for 5 min, mechanically stirred for 1 min, and then ultrasonically dispersed again for 3 min. Alternating between mechanical stirring and ultrasonic dispersion facilitates the dispersion of soft magnetic powder agglomerates and reduces localized temperature rise caused by continuous ultrasonication.

[0038] Furthermore, the amount of aluminum isopropoxide added is determined according to the theoretical mass of Al2O3 obtained from its complete conversion, wherein the theoretical mass of Al2O3 is 0.2% to 1.2% of the mass of the soft magnetic powder.

[0039] Preferably, the theoretical mass of Al2O3 is 0.4% to 1.0% of the mass of the soft magnetic powder.

[0040] More preferably, the theoretical mass of the Al2O3 is 0.8% of the mass of the soft magnetic powder.

[0041] Furthermore, the molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water is 1:0.8-1.2:2.5-3.5.

[0042] Preferably, the molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water is 1:1:3.

[0043] This invention selects glacial acetic acid as the complexation regulator for aluminum isopropoxide. On one hand, glacial acetic acid has a low water content, preventing the introduction of large amounts of unmeasured water when added to the aluminum isopropoxide system. This allows the complexation regulation process of aluminum isopropoxide by glacial acetic acid to be separated from the hydrolysis process initiated by deionized water. On the other hand, the acetate ions in glacial acetic acid can coordinate with the aluminum centers of aluminum isopropoxide and partially replace the isopropoxy groups, forming modified aluminum alkoxide species containing acetate ions. Compared to unmodified aluminum isopropoxide, the modified aluminum alkoxide species have relatively lower reactivity with water, thus slowing down the hydrolysis rate of aluminum isopropoxide and reducing the rapid nucleation and free precipitation of aluminum-containing species in solution.

[0044] Glacial acetic acid also has the characteristics of simple molecular structure, can be mixed with isopropanol and does not introduce inorganic ions such as metal ions and chloride ions. Its organic components can be gradually decomposed or removed during subsequent drying and heat treatment, so it is suitable for the preparation of aluminum precursor coating layers on the surface of soft magnetic powder.

[0045] The molar ratio of glacial acetic acid to aluminum isopropoxide is controlled at 0.8–1.2:1 to ensure sufficient acetate groups to coordinate with aluminum centers in the system, while avoiding excessive or insufficient addition of glacial acetic acid. Insufficient glacial acetic acid may lead to inadequate complexation modification of aluminum isopropoxide, resulting in rapid hydrolysis upon contact with water. Excessive glacial acetic acid increases the number of acetate species and organic components in the system, potentially excessively inhibiting the hydrolysis and condensation of aluminum-containing species, which is detrimental to the deposition of aluminum hydrolysis products on the soft magnetic powder surface and subsequent inorganic transformation. Therefore, maintaining a molar ratio of glacial acetic acid to aluminum isopropoxide at 0.8–1.2:1 is beneficial for achieving a balance between the hydrolysis rate and the surface deposition process.

[0046] Aluminum isopropoxide molecules contain three hydrolyzable isopropoxy groups. According to the reaction relationship where aluminum isopropoxide completely hydrolyzes to form hydroxyl-containing aluminum species, theoretically, three moles of water are required per mole of aluminum isopropoxide. Therefore, this invention centers on a molar ratio of aluminum isopropoxide to deionized water of 1:3, controlling the molar ratio between the two to be 1:2.5–3.5.

[0047] When the relative amount of deionized water added is too small, the isopropoxy groups in aluminum isopropoxide may not hydrolyze sufficiently, which is not conducive to the subsequent condensation and surface deposition of aluminum-containing species. When the relative amount of deionized water added is too large, even with dilution with isopropanol, the local water concentration in the reaction system may still increase, causing aluminum isopropoxide to undergo rapid homogeneous hydrolysis, thereby increasing the tendency for free aluminum-containing precipitates and agglomerates to form. Therefore, controlling the molar ratio of aluminum isopropoxide to deionized water at 1:2.5 to 3.5 is beneficial for balancing the degree and rate of hydrolysis of aluminum isopropoxide.

[0048] When the molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water is 1:1:3, each mole of aluminum isopropoxide corresponds to one mole of glacial acetic acid and three moles of deionized water. This ensures that the degree of complexation modification of aluminum isopropoxide by glacial acetic acid matches the theoretical water requirement for the hydrolysis of aluminum isopropoxide. This facilitates more complete hydrolysis of aluminum isopropoxide under complexation-controlled conditions and promotes the deposition of aluminum-containing hydrolysis products on the surface of soft magnetic powder.

[0049] Further, aluminum isopropoxide is added to isopropanol, wherein the mass ratio of the soft magnetic powder to the volume of isopropanol used to disperse or dissolve aluminum isopropoxide is 1 g: 1-3 mL, and the mixture is stirred at 20°C-30°C for 20-40 min; then glacial acetic acid is added and stirring is continued for 20-40 min to obtain the aluminum source solution.

[0050] In this invention, the ratio of magnetic powder mass to isopropanol volume used for dispersing or dissolving aluminum isopropoxide is set to 1 g: 1-3 mL. When the amount of isopropanol is too small, the aluminum isopropoxide concentration is high, which can easily lead to excessively rapid local reactions during subsequent complexation and hydrolysis. When the amount of isopropanol is too large, the system is overly diluted, which is not conducive to the subsequent deposition of aluminum-containing species on the surface of the soft magnetic powder and increases the subsequent solvent evaporation time. Therefore, controlling it within the above range is beneficial to balance the stability of the aluminum source system, coating efficiency, and process efficiency.

[0051] Preferably, the ratio of the mass of the soft magnetic powder to the volume of isopropanol used to disperse or dissolve aluminum isopropoxide is 1 g: 2 mL; the mixture is stirred for 30 min before and after adding glacial acetic acid.

[0052] Furthermore, isopropanol is used to dilute the deionized water. The ratio of the mass of the soft magnetic powder to the volume of isopropanol used to dilute the deionized water is 1g:0.3mL to 0.8mL. This range can reduce the local water concentration while avoiding the reduction of aluminum species concentration and surface deposition driving force due to excessive dilution, and also takes into account the subsequent solvent removal efficiency.

[0053] Isopropanol was used to dilute the deionized water in order to reduce the local water concentration in the reaction system during the addition of deionized water and to reduce the rapid homogeneous hydrolysis of aluminum isopropoxide.

[0054] Preferably, the ratio of the mass of the soft magnetic powder to the volume of isopropanol used to dilute the deionized water is 1 g: 0.5 mL.

[0055] Further, deionized water diluted with isopropanol is slowly added dropwise to the aluminum source solution over a period of 20 to 25 minutes; after the addition is complete, stirring is continued for 10 to 15 minutes.

[0056] The dropping time is used to control the rate at which water enters the aluminum source solution. Slow dropping keeps the water concentration and supply rate in the aluminum source system at a low level, thereby reducing the tendency for rapid homogeneous hydrolysis of aluminum isopropoxide and promoting the gradual formation and migration and deposition of aluminum-containing species onto the soft magnetic powder surface. Continued stirring after dropping is completed allows the aluminum-containing species in the system to undergo further hydrolysis and condensation, forming a relatively stable aluminum-containing precursor solution.

[0057] Furthermore, the aluminum-containing precursor liquid is added to the soft magnetic powder suspension for 10 to 15 minutes; after the addition is completed, the mixture is reacted at 40 to 50 degrees Celsius with continuous stirring for 1 to 2 hours, followed by static aging for 20 to 30 minutes.

[0058] The aluminum-containing precursor solution of this invention is added to the soft magnetic powder suspension for 10 to 15 minutes. If the addition time is too short, the local concentration of aluminum-containing species in the reaction system may increase rapidly, easily leading to excessively rapid local deposition and uneven coating thickness. If the addition time is too long, some aluminum-containing species in the precursor solution may continue to condense and aggregate in the liquid phase, reducing their efficiency in migrating and depositing on the surface of the soft magnetic powder. Therefore, controlling the addition time to 10 to 15 minutes is beneficial for balancing the surface deposition rate of aluminum-containing species and system stability, resulting in a more uniform aluminum-containing precursor coating.

[0059] Preferably, after the material is added, the reaction is carried out at 45°C and under continuous stirring for 1.5 hours, followed by static aging for 20 to 30 minutes.

[0060] This invention controls the reaction temperature of the aluminum-containing precursor liquid and the soft magnetic powder suspension at 40℃~50℃. Appropriately increasing the reaction temperature can improve the rate of hydrolysis and condensation reactions in the aluminum-containing precursor system and promote the diffusion and deposition of aluminum-containing species onto the surface of the soft magnetic powder, avoiding the need for a long reaction time due to the slow reaction rate at room temperature or lower temperatures.

[0061] When the reaction temperature is too low, the hydrolysis, condensation, and surface deposition rates of aluminum-containing species are relatively low, and it may be difficult to form a relatively complete aluminum-containing precursor coating layer within a limited reaction time. When the reaction temperature is too high, the hydrolysis and condensation reactions of aluminum-containing species in the solution may be too fast, thereby increasing the tendency for homogeneous nucleation, free precipitation, and agglomeration. At the same time, it may also accelerate the volatilization of anhydrous ethanol and isopropanol, causing rapid changes in the solvent composition and aluminum-containing species concentration of the reaction system, which is not conducive to the stable control of the coating process.

[0062] The preferred reaction temperature is 45°C. This temperature provides an appropriate reaction rate for the hydrolysis, condensation, and surface deposition of aluminum-containing species. Furthermore, it is below the boiling points of anhydrous ethanol and isopropanol, minimizing changes in system composition caused by significant solvent evaporation. Therefore, 45°C facilitates a balance between reaction rate, solution stability, and soft magnetic powder surface deposition.

[0063] Continuous stirring is maintained during the reaction to keep the soft magnetic powder in a suspended and dispersed state in the reaction system and to ensure that the aluminum-containing precursor solution is uniformly distributed in the soft magnetic powder suspension. Continuous stirring also reduces the local concentration difference of aluminum-containing species near the surface of the soft magnetic powder, promotes the continuous transfer of aluminum-containing species from the reaction system to the surface of the soft magnetic powder, and reduces the tendency of soft magnetic powder to settle, local coating enrichment, and particle adhesion and agglomeration.

[0064] The reaction time is controlled within 1 to 2 hours to provide sufficient time for the hydrolysis, condensation, and deposition of aluminum-containing species on the surface of soft magnetic powder. If the reaction time is too short, the aluminum-containing hydrolysis products may not be fully deposited; if the reaction time is too long, the aluminum-containing species in the reaction system may continue to undergo solution phase condensation, increasing the tendency for free particles and agglomerates to form.

[0065] Preferably, the reaction is carried out at 45°C and under continuous stirring for 1.5 hours to coordinate the reaction rate of the aluminum-containing precursor with the deposition process on the surface of the soft magnetic powder. Subsequently, the deposited aluminum-containing species are further condensed and stabilized by static aging to form an aluminum-containing precursor coating layer.

[0066] Furthermore, after aging is complete, the reaction system is not filtered, centrifuged, or washed. Instead, isopropanol, anhydrous ethanol, and other volatile components in the reaction system continue to evaporate under heating and stirring conditions until the reaction system forms a wet powder.

[0067] By eliminating solid-liquid separation and washing, the loss of aluminum-containing precursors that have been deposited or are still in a dispersed state during the separation and washing process can be reduced, and it is also beneficial to maintain a corresponding relationship between the amount of aluminum isopropoxide added and the amount of aluminum-containing material ultimately retained in the soft magnetic powder system.

[0068] Further, the obtained wet powder is dried in air at 60℃~90℃ for 4h~12h, then ground and sieved.

[0069] The drying process is used to remove residual solvents and moisture from the wet powder; the grinding and sieving process is used to break up agglomerates formed during the drying process, so that the coated powder has a particle size suitable for subsequent heat treatment and molding.

[0070] Preferably, the obtained wet powder is dried at 80°C for 8 hours, then ground and passed through a 150-mesh sieve.

[0071] Furthermore, the protective atmosphere is nitrogen or an inert gas; the heat treatment temperature and holding time are determined according to the material type of the soft magnetic powder and its heat treatment regime, and the aluminum-containing precursor coating layer is transformed into an aluminum-containing inorganic insulating layer.

[0072] Furthermore, when the soft magnetic powder is FeSiBCuNb amorphous soft magnetic powder, it is heated to 580℃~620℃ at a heating rate of 2℃ / min~6℃ / min under a nitrogen protective atmosphere, held at that temperature for 2h~4h, and then cooled with the furnace.

[0073] Preferably, the temperature is increased to 600°C at a heating rate of 4°C / min, held for 3 hours, and then cooled with the furnace.

[0074] When the soft magnetic powder is FeSiBCuNb amorphous soft magnetic powder, the heat treatment simultaneously causes the FeSiBCuNb amorphous soft magnetic powder to undergo nanocrystallization and causes the aluminum-containing precursor coating layer to undergo inorganic transformation, thereby completing the soft magnetic powder structure regulation and the formation of the aluminum-containing inorganic insulating layer in a single heat treatment process.

[0075] Furthermore, the adhesive is selected from one or more of modified silicone resin, epoxy resin, polyimide adhesive and polyurethane adhesive; the organic solvent is an organic solvent capable of dissolving or dispersing the adhesive.

[0076] Preferably, the adhesive is a modified silicone resin and the organic solvent is acetone.

[0077] Furthermore, the amount of adhesive added is 0.5% to 4% of the mass of the soft magnetic powder coated with the aluminum insulating layer, and the amount of adhesive added is based on the mass of the solid components of the adhesive.

[0078] Preferably, the amount of adhesive added is 1% to 3% of the mass of the soft magnetic powder coated with the aluminum insulating layer.

[0079] More preferably, the amount of adhesive added is 2% of the mass of the soft magnetic powder coated with the aluminum insulating layer.

[0080] Furthermore, the granulated soft magnetic powder is pressed into shape under a pressure of 800MPa to 1800MPa.

[0081] Preferably, the granulated soft magnetic powder is pressed into shape under a pressure of 1200 MPa.

[0082] Furthermore, the protective atmosphere is nitrogen or an inert gas; the curing and annealing temperatures are determined based on the curing temperature and heat resistance properties of the adhesive.

[0083] Furthermore, when the binder is a modified silicone resin, it is heated to 180°C to 220°C at a heating rate of 2°C / min to 6°C / min under a nitrogen protective atmosphere, held at that temperature for 2h to 4h, and then cooled in the furnace.

[0084] Preferably, the temperature is increased to 200°C at a heating rate of 4°C / min, held for 3 hours, and then cooled with the furnace.

[0085] Secondly, the present invention provides a soft magnetic composite material coated with an aluminum insulating layer, wherein the soft magnetic composite material is prepared by the above-described preparation method.

[0086] Furthermore, the soft magnetic composite material includes soft magnetic powder particles, an aluminum-containing inorganic insulating layer disposed on the surface of the soft magnetic powder particles, and a binder distributed on the surface of the soft magnetic powder particles and between adjacent soft magnetic powder particles.

[0087] Furthermore, the soft magnetic powder particles are FeSiBCuNb nanocrystalline soft magnetic powder particles, the aluminum-containing inorganic insulating layer is an aluminum oxide-containing inorganic insulating layer, and the binder is a modified organosilicon resin.

[0088] The theoretical Al2O3 content mentioned in this invention refers to the percentage of the theoretical mass of Al2O3 relative to the mass of the soft magnetic powder before coating, calculated based on the assumption that all aluminum in aluminum isopropoxide is converted into Al2O3. The theoretical Al2O3 content is used to determine the amount of aluminum isopropoxide added and does not represent the actual Al2O3 content on the surface of the soft magnetic powder obtained through testing.

[0089] According to the law of conservation of substance for aluminum, two moles of aluminum isopropoxide correspond to one mole of Al₂O₃. The theoretical amount of aluminum isopropoxide to be added is calculated using the following formula: m1 = m0 × w × 2M1 ÷ M2 ÷ P; In the formula, m1 is the actual mass of aluminum isopropoxide added; m0 is the mass of the soft magnetic powder before coating; w is the target theoretical Al2O3 content; M1 is the molar mass of aluminum isopropoxide; M2 is the molar mass of Al2O3; and P is the mass purity of the aluminum isopropoxide reagent, which is used in the calculation in decimal form.

[0090] The molar mass of aluminum isopropoxide is approximately 204.24 g / mol, and the molar mass of Al₂O₃ is approximately 101.96 g / mol. Without considering reagent purity corrections, the mass of aluminum isopropoxide required to form a unit mass of theoretical Al₂O₃ is approximately 4.006 times the required mass. In actual preparation, the amount added should be corrected according to the nominal purity of the aluminum isopropoxide reagent.

[0091] The amount of adhesive added according to this invention is based on the mass of the solid components of the adhesive. When the adhesive is added in solution form, the actual amount of adhesive added is calculated based on the solid content of the adhesive solution.

[0092] In this embodiment of the invention, FeSiBCuNb amorphous soft magnetic powder is used as a representative soft magnetic powder. The chemical composition of the FeSiBCuNb amorphous soft magnetic powder, by mass percentage, includes: Si: 3%~4%, B: 1%~2%, Cu: 1%~2%, Nb: 6%~7%, with the balance being Fe.

[0093] The controlled hydrolysis and surface deposition process of this invention is not limited to FeSiBCuNb amorphous soft magnetic powder. In other embodiments, the soft magnetic powder can be replaced with Fe-Si, Fe-Si-Al, Fe-Si-Cr, Fe-Ni, Fe-Co, or other iron-based soft magnetic powders. When using other types of soft magnetic powders, the pre-drying conditions, dispersion medium dosage, and heat treatment conditions can be adjusted accordingly based on the particle size, surface condition, oxidation sensitivity, and applicable heat treatment regime of the soft magnetic powder.

[0094] When soft magnetic powder does not require crystallization, the heat treatment step is mainly used to dehydrate, decompose, and inorganically transform the aluminum precursor coating layer. When the soft magnetic powder is an amorphous soft magnetic powder that needs to form a nanocrystalline structure through heat treatment, heat treatment conditions that match the crystallization regime of the soft magnetic powder can be selected to simultaneously complete the microstructure control of the soft magnetic powder and the inorganic transformation of the aluminum precursor coating layer.

[0095] In this embodiment of the invention, based on 100 parts by mass of FeSiBCuNb amorphous soft magnetic powder, the amount of aluminum isopropoxide corresponding to different theoretical Al2O3 contents is shown in Table 1.

[0096] To better understand the above technical solutions, exemplary embodiments of the present invention will be described in more detail below. It should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.

[0097] Table 1. Theoretical Al2O3 content of each embodiment and comparative example

[0098] Example 1 This embodiment provides a FeSiBCuNb soft magnetic powder with an aluminum insulating layer and a theoretical Al2O3 content of 0.2wt%, and its preparation method, which specifically includes the following steps.

[0099] Step 1: Place the FeSiBCuNb amorphous soft magnetic powder in an air atmosphere oven and pre-dry it at 65°C for 2 hours to remove the moisture adsorbed on the surface of the soft magnetic powder and reduce the influence of surface adsorbed water on the subsequent controlled hydrolysis process of aluminum isopropoxide.

[0100] Pre-dried FeSiBCuNb amorphous soft magnetic powder was added to anhydrous ethanol at a mass ratio of 1 g to 4.5 mL. The powder was first thoroughly wetted by mechanical stirring, then ultrasonically dispersed for 5 min, mechanically stirred for 1 min, and then ultrasonically dispersed for another 3 min to obtain a uniformly dispersed FeSiBCuNb amorphous soft magnetic powder suspension.

[0101] Mechanical stirring and ultrasonic dispersion are performed alternately to break up soft magnetic powder agglomerates and fully disperse the soft magnetic powder in anhydrous ethanol, while reducing the local temperature rise that may be caused by continuous ultrasound.

[0102] The amount of aluminum isopropoxide added is calculated based on the theoretical mass of Al2O3 obtained from the complete conversion of aluminum isopropoxide being 0.2% of the mass of FeSiBCuNb amorphous soft magnetic powder.

[0103] Add aluminum isopropoxide to isopropanol, with a magnetic powder mass to isopropanol volume ratio of 1 g: 2 mL. Stir at 20℃-30℃ for 30 min to ensure the aluminum isopropoxide is fully dispersed or dissolved.

[0104] Add glacial acetic acid at a molar ratio of aluminum isopropoxide to glacial acetic acid of 1:1, and continue stirring for 30 minutes to allow the glacial acetic acid to complex and regulate the aluminum isopropoxide, thus obtaining an aluminum source solution.

[0105] The amount of deionized water added was determined according to a molar ratio of aluminum isopropoxide to deionized water of 1:3, and the deionized water was diluted with isopropanol. The ratio of the mass of magnetic powder to the volume of isopropanol used to dilute the deionized water was 1 g: 0.5 mL.

[0106] Under continuous stirring, deionized water diluted with isopropanol was slowly added dropwise to the aluminum source solution over a period of 20–25 minutes. After the addition was complete, stirring was continued for 10–15 minutes to allow controlled pre-hydrolysis of aluminum isopropoxide, yielding an aluminum-containing precursor solution.

[0107] Step 2: Slowly add the aluminum-containing precursor liquid to the ultrasonically dispersed FeSiBCuNb amorphous soft magnetic powder suspension over a period of 10 to 15 minutes.

[0108] After the feed is completed, the reaction is carried out at 45°C and under continuous stirring for 1.5 hours, so that the aluminum-containing hydrolysis products are deposited on the surface of FeSiBCuNb amorphous soft magnetic powder to form an aluminum-containing precursor coating layer.

[0109] After the reaction is complete, allow it to stand for aging for 20 to 30 minutes.

[0110] After aging, the reaction system is not subjected to solid-liquid separation and washing. Instead, isopropanol, anhydrous ethanol, and other volatile components in the system are gradually evaporated under heating and stirring conditions until the system forms a wet powder.

[0111] By eliminating solid-liquid separation and washing, the process minimizes the loss of deposited or still dispersed aluminum-containing precursors during separation and washing, and maintains a relatively stable correlation between the amount of aluminum isopropoxide added and the final amount of aluminum-containing material retained in the soft magnetic powder system. Furthermore, it avoids mechanical disturbance to the incompletely condensed and solidified aluminum-containing precursor coating layer during filtration, centrifugation, and washing, thus preserving the continuity and integrity of the coating layer and reducing the tendency for localized coating layer detachment or particle re-agglomeration. Simultaneously, this process reduces solid-liquid separation and washing steps, simplifying the preparation process and facilitating continuous and large-scale production.

[0112] The obtained wet powder was placed in an air-atmosphere oven and dried at 80°C for 8 hours to remove residual solvent and moisture. The dried powder was then ground and sieved to break up agglomerates formed during the drying process, yielding FeSiBCuNb amorphous soft magnetic powder with an aluminum precursor coating.

[0113] Step 3: Place the FeSiBCuNb amorphous soft magnetic powder with an aluminum precursor coating in a tube furnace for heat treatment, that is, heat it to 600°C under a nitrogen protective atmosphere, hold it for 3 hours, and then cool it with the furnace.

[0114] Through the above-mentioned heat treatment crystallization annealing, FeSiBCuNb amorphous soft magnetic powder is made into a nanocrystalline structure, while the aluminum-containing precursor coating layer undergoes dehydration, decomposition and inorganic transformation, resulting in FeSiBCuNb soft magnetic powder with an aluminum oxide inorganic insulating layer.

[0115] Nitrogen protective atmosphere is used to reduce excessive oxidation of FeSiBCuNb soft magnetic powder during heat treatment; controlling the heating rate is used to reduce the impact of rapid temperature changes on the microstructure transformation of soft magnetic powder and the inorganicization process of the coating layer. Step 4: Add the heat-treated aluminum-containing insulating layer-coated FeSiBCuNb soft magnetic powder to acetone, and then add 2% (by weight of the soft magnetic powder) of modified organosilicon resin. The amount of modified organosilicon resin added is based on the mass of the resin solids.

[0116] Continuous stirring allows the modified silicone resin to distribute on the surface of the soft magnetic powder particles. Acetone is then removed by heating and stirring, and the powder is dried and granulated to obtain the granulated powder to be pressed.

[0117] An aluminum-containing inorganic insulating layer and a modified silicone resin together constitute an inorganic-organic composite insulation system. The aluminum-containing inorganic insulating layer is used to improve the insulation and heat resistance between particles, while the modified silicone resin is used to further isolate adjacent particles and improve the structural stability of the material after compression molding.

[0118] Step 5: Load the granulated powder into a mold and press it into shape under a pressure of 1200MPa using a cold pressing method to obtain a soft magnetic composite material blank.

[0119] The soft magnetic composite material blank was placed in an annealing furnace and heated to 200°C at a heating rate of 4°C / min under a nitrogen protective atmosphere. The temperature was held for 3 hours and then cooled with the furnace to obtain FeSiBCuNb soft magnetic composite material with an aluminum insulating layer.

[0120] The treatment is used to further cure the modified silicone resin and release some of the internal stress generated during the compression molding process.

[0121] Example 2 The difference between this embodiment and Example 1 is that the amount of aluminum isopropoxide added is determined based on the theoretical mass of Al2O3 obtained from its complete conversion being 0.4% of the mass of FeSiBCuNb amorphous soft magnetic powder.

[0122] The molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water remains 1:1:3, and the proportions of other raw materials, preparation steps, and process parameters are the same as in Example 1.

[0123] Example 3 The difference between this embodiment and Embodiment 1 is that the amount of aluminum isopropoxide added is determined based on the theoretical mass of Al2O3 obtained from its complete conversion being 0.6% of the mass of FeSiBCuNb amorphous soft magnetic powder.

[0124] The molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water remains 1:1:3, and the proportions of other raw materials, preparation steps, and process parameters are the same as in Example 1.

[0125] Example 4 The difference between this embodiment and Example 1 is that the amount of aluminum isopropoxide added is determined according to the theoretical mass of Al2O3 obtained from its complete conversion being 0.8% of the mass of FeSiBCuNb amorphous soft magnetic powder.

[0126] The molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water remains 1:1:3, and the proportions of other raw materials, preparation steps, and process parameters are the same as in Example 1.

[0127] Example 5 The difference between this embodiment and Example 1 is that the amount of aluminum isopropoxide added is determined according to the theoretical mass of Al2O3 obtained from its complete conversion being 1.0% of the mass of FeSiBCuNb amorphous soft magnetic powder.

[0128] The molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water remains 1:1:3, and the proportions of other raw materials, preparation steps, and process parameters are the same as in Example 1.

[0129] Example 6 The difference between this embodiment and Example 1 is that the amount of aluminum isopropoxide added is determined according to the theoretical mass of Al2O3 obtained from its complete conversion being 1.2% of the mass of FeSiBCuNb amorphous soft magnetic powder.

[0130] The molar ratio of aluminum isopropoxide, glacial acetic acid, and deionized water remains 1:1:3, and the proportions of other raw materials, preparation steps, and process parameters are the same as in Example 1.

[0131] Example 7 The only difference between this embodiment and Example 3 is that the FeSiBCuNb amorphous soft magnetic powder is replaced with FeNi alloy soft magnetic powder, wherein the Ni content of the FeNi alloy soft magnetic powder is 50wt% and the median particle size D50 is 3.82μm; the remaining raw material amounts and process conditions are the same as in Example 3. The amount of aluminum isopropoxide added is determined according to the theoretical Al2O3 content obtained after its complete conversion being 0.6% of the mass of the FeNi alloy soft magnetic powder, thus obtaining an aluminum-insulating layer-coated FeNi soft magnetic composite material.

[0132] Example 8 The only difference between this embodiment and Embodiment 3 is that the FeSiBCuNb amorphous soft magnetic powder is replaced with FeSiBCrC amorphous soft magnetic powder, the median particle size D50 of which is 11.84 μm. During the inorganic heat treatment of the aluminum precursor coating layer, the temperature is raised to 500°C at a rate of 4°C / min under a nitrogen protective atmosphere, held for 0.5 h, and then cooled in the furnace. All other raw material amounts and process conditions are the same as in Embodiment 3. The amount of aluminum isopropoxide added is determined based on the theoretical Al2O3 content obtained from its complete conversion being 0.6% of the mass of the FeSiBCrC amorphous soft magnetic powder, resulting in an aluminum-insulating FeSiBCrC soft magnetic composite material.

[0133] Comparative Example 1 Comparative Example 1 used the same FeSiBCuNb amorphous soft magnetic powder, solvent ratio, amount of glacial acetic acid, amount of deionized water, ultrasonic dispersion, heating and stirring, aging, solvent evaporation, drying, grinding, sieving, crystallization annealing, resin coating, granulation, pressing and low-temperature annealing process as Example 1.

[0134] The only difference between Comparative Example 1 and Example 1 is that aluminum isopropoxide is not added, thus preventing the formation of an aluminum-containing precursor coating layer on the surface of the FeSiBCuNb amorphous soft magnetic powder. The theoretical Al2O3 content of Comparative Example 1 is 0.

[0135] Comparative Example 2 The only difference between this comparative example and Example 1 is that glacial acetic acid is not added during the preparation of the aluminum source solution, and isopropanol of the same volume as glacial acetic acid in Example 1 is used instead. The amounts of other raw materials and process conditions are the same as in Example 1.

[0136] Specifically, aluminum isopropoxide was weighed according to the theoretical mass of Al2O3 obtained from the complete conversion of aluminum isopropoxide being 0.2% of the mass of the soft magnetic powder. Aluminum isopropoxide was added to isopropanol and stirred at 20°C–30°C for 30 min. Then, an equal volume of isopropanol as used in Example 1 was added, and stirring continued for another 30 min. The amount of deionized water added was determined according to a molar ratio of aluminum isopropoxide to deionized water of 1:3. The deionized water was diluted with isopropanol and slowly added dropwise to the aluminum isopropoxide dispersion over 20–25 min. After the addition was complete, stirring continued for 10–15 min to obtain an aluminum-containing precursor solution without the complexation control of glacial acetic acid.

[0137] Subsequently, following the same feeding method as in Example 1, the aluminum-containing precursor liquid was added to the soft magnetic powder suspension, and the following processes were carried out in sequence: reaction at 45°C, static aging, direct solvent evaporation, drying, grinding, sieving, heat treatment, binder coating, granulation, pressing and molding, and curing and annealing, to obtain the soft magnetic composite material of Comparative Example 2.

[0138] Power loss tests were performed on the soft magnetic composite materials prepared in Examples 1-8 and Comparative Examples 1-2, respectively.

[0139] All groups of magnetic powder cores were prepared using the same mold, powder loading method, and pressing process, resulting in magnetic powder cores with consistent geometric dimensions and minimal density differences. All samples were tested using the same winding method and testing instrument.

[0140] All power loss data are averages of test results from multiple magnetic powder cores. Table 2 shows the losses and permeabilities of the high-frequency, low-iron-loss soft magnetic composite materials prepared in Comparative Examples 1-2 and Examples 1-8.

[0141] Table 2 Power loss and permeability of soft magnetic composite materials with different theoretical Al2O3 contents Table 2 shows that the theoretical Al2O3 content of Comparative Example 2 and Example 1 is 0.2 wt%, the difference being that Comparative Example 2 did not add glacial acetic acid. Under conditions of 20 mT and 1 MHz, the power loss decreased from 280.31 kW / m² after adding glacial acetic acid. 3 Reduced to 250.92kW / m 3 The decrease was approximately 10.48%; under conditions of 50mT and 500kHz, the power loss decreased from 1111.93kW / m 3 Reduced to 1102.45kW / m 3 The permeability only changed from 20.80 to 20.72. This indicates that glacial acetic acid is beneficial for controlling the hydrolysis and condensation process of aluminum isopropoxide, improving the aluminum-containing insulation coating effect, and further reducing high-frequency power loss while basically maintaining the permeability.

[0142] Compared to Comparative Example 1 without aluminum insulation coating, Examples 1-6 showed a power loss reduction of approximately 29.72%-39.66% at 20mT and 1MHz, and a reduction of approximately 1.32%-5.42% at 50mT and 500kHz; their permeability was 20.30-20.91, with a maximum reduction of approximately 3.15% compared to 20.96 in Comparative Example 1. Examples 7-8 also showed a power loss reduction of approximately 36% at 20mT and 1MHz compared to the uncoated example, which is within the normal range.

[0143] With increasing theoretical Al2O3 content, the power loss of the soft magnetic composite material generally showed a trend of first decreasing and then increasing. Among them, Example 4, with a theoretical Al2O3 content of 0.8wt%, exhibited better overall performance, with its power loss decreasing from 357.05kW / m in Comparative Example 1 under conditions of 20mT and 1MHz. 3 Reduced to 215.45 kW / m3 The power loss was approximately 39.66% at 50 mT and 500 kHz; the power loss was approximately 5.42% at 50 mT and 500 kHz, while the permeability remained at 20.79. The results indicate that adding glacial acetic acid and controlling the theoretical Al₂O₃ content within a suitable range can achieve a good balance between reducing high-frequency power loss and maintaining permeability.

[0144] Based on the combined results of the two test conditions and the permeability test, Example 4, with a theoretical Al2O3 content of 0.8 wt%, exhibits lower power loss while maintaining a permeability similar to the comparative example. This demonstrates that controlling the theoretical Al2O3 content within a suitable range can achieve a good balance between improving interparticle insulation performance and maintaining soft magnetic properties. The above examples are merely preferred embodiments of the present invention. Those skilled in the art can adjust or equivalently substitute the dispersion medium dosage, reaction temperature, reaction time, drying conditions, heat treatment conditions, binder type, and molding process based on the type of soft magnetic powder, powder particle size, surface condition, and heat treatment regime, without departing from the technical concept of the present invention.

[0145] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a soft magnetic composite material coated with an aluminum insulating layer, characterized in that, Includes the following steps: Step S1: Pre-dry the soft magnetic powder and add anhydrous ethanol and stir to obtain a soft magnetic powder suspension; add aluminum isopropoxide to isopropanol, then add glacial acetic acid and stir to obtain an aluminum source solution; dilute deionized water with isopropanol and add it to the aluminum source solution and stir to obtain an aluminum-containing precursor solution. Step S2: Add the aluminum-containing precursor liquid to the soft magnetic powder suspension, and age it after stirring under heating conditions; After aging, the reaction system is not subjected to solid-liquid separation and washing. Instead, the solvent in the reaction system is directly evaporated by heating and stirring of the suspension. After drying, soft magnetic powder with an aluminum-containing precursor coating structure is obtained. Step S3: Under a protective atmosphere, the soft magnetic powder with an aluminum-containing precursor coating structure is heat-treated to obtain a soft magnetic powder with an aluminum insulating layer coating. Step S4: Mix the soft magnetic powder with aluminum insulating layer and binder in an organic solvent, so that the binder is distributed on the surface of the soft magnetic powder with aluminum insulating layer. Remove the organic solvent and dry it to obtain a soft magnetic powder with a multi-layer coating structure. Step S5: Press the soft magnetic powder with a multi-layer coating structure on the surface into shape, and anneal it in a protective gas atmosphere to obtain a soft magnetic composite material with an aluminum insulating layer.

2. The method for preparing the soft magnetic composite material coated with an aluminum insulating layer according to claim 1, characterized in that, The soft magnetic powder is selected from iron-based soft magnetic powder.

3. The method for preparing the soft magnetic composite material coated with an aluminum insulating layer according to claim 2, characterized in that, The iron-based soft magnetic powder is selected from one or more of the following: Fe-Si soft magnetic powder, Fe-Si-Al soft magnetic powder, Fe-Si-Cr soft magnetic powder, Fe-Ni soft magnetic powder, and Fe-Co soft magnetic powder.

4. The method for preparing the soft magnetic composite material coated with an aluminum insulating layer according to claim 1, characterized in that, In step S1, the mass ratio of the soft magnetic powder to the volume of anhydrous ethanol is 1g:3mL to 6mL.

5. The method for preparing the soft magnetic composite material coated with an aluminum insulating layer according to claim 1, characterized in that, The amount of aluminum isopropoxide added is determined according to the theoretical mass of Al2O3 obtained from its complete conversion, and the theoretical mass of Al2O3 is 0.2% to 1.2% of the mass of the soft magnetic powder; the molar ratio of aluminum isopropoxide, glacial acetic acid and deionized water is 1:0.8 to 1.2:2.5 to 3.5; the mass ratio of the soft magnetic powder to the volume of isopropanol used to disperse or dissolve aluminum isopropoxide is 1g:1mL to 3mL, and the mixture is stirred at 20℃ to 30℃ for 20min to 40min; then glacial acetic acid is added and stirring is continued for 20min to 40min to obtain the aluminum source solution; the mass ratio of the soft magnetic powder to the volume of isopropanol used to dilute the deionized water is 1g:0.5mL.

6. The method for preparing the soft magnetic composite material coated with an aluminum insulating layer according to claim 1, characterized in that, The aluminum-containing precursor solution is added to the soft magnetic powder suspension for 10 to 15 minutes; after addition, the mixture is reacted at 40 to 50 degrees Celsius with continuous stirring for 1 to 2 hours, followed by static aging for 20 to 30 minutes.

7. The method for preparing the soft magnetic composite material coated with an aluminum insulating layer according to claim 1, characterized in that, When the soft magnetic powder is FeSiBCuNb amorphous soft magnetic powder, the heat treatment is carried out under a nitrogen protective atmosphere, with the temperature increased to 580℃~620℃ at a heating rate of 2℃ / min~6℃ / min, held for 2h~4h, and then cooled in the furnace.

8. A soft magnetic composite material coated with an aluminum insulating layer, characterized in that, Prepared by any of the preparation methods described in claims 1-7; The soft magnetic composite material covered by the aluminum-containing insulating layer includes soft magnetic powder particles, an aluminum-containing inorganic insulating layer disposed on the surface of the soft magnetic powder particles, and a binder distributed on the surface of the soft magnetic powder particles and between adjacent soft magnetic powder particles.

9. The soft magnetic composite material coated with an aluminum insulating layer according to claim 8, characterized in that, The soft magnetic powder particles are FeSiBCuNb nanocrystalline soft magnetic powder particles, the aluminum-containing inorganic insulating layer is an aluminum oxide-containing inorganic insulating layer, and the binder is a modified organosilicon resin.

Citation Information

Patent Citations

  • Preparation method of coated type soft magnetic powder core

    CN108242311A

  • Method for coating surface of metal soft magnetic powder with lithium aluminum oxide insulating layer in situ

    CN110434326A

  • Phosphoric acid-silane co-coated metal soft magnetic composite material and preparation method thereof

    CN111354528A